EFFECT OF IODINE DEFICIENCY ON PHYSIOLOGICAL AND HEMATOLOGICAL PARAMETERS IN COWS UNDER FIELD CONDITIONS - Das, Shilpi; Rehman, Atiqur (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A Study was undertaken to estimate haematological changes in iodine deficient cows of Himalayan belt. There was significant decrease in all physiological and haematological parameters of iodine deficient cows.